(untitled) - Barton, Robert (New Jersey, 2003)
The book presents a practical approach for initiating and reinforcing global IT, focusing on the mechanisms that need to be put in place to effectively manage IT architecture, strategy, standards, and control across sites in a multinational firm. Key considerations are explained for each domain together with concrete recommendations for core organisation, processes and deliverables. The approach fits cleanly into established best practices for IT such as the CobiTr framework for IT management
Keywords: Information technology,International business enteprises,Management informations systems,Computer architecture,Strategic planning; Management,Communication systems,Management